Liver Transplantation for Glycogen Storage Disease Type IV - Liu, Min; Sun, Li-Ying (Frontiers in Pediatrics, 2021)
Glycogen storage disease type IV (GSD IV) is a rare autosomal recessive disorder caused by glycogen–branching enzyme (GBE) deficiency, leading to accumulation of amylopectin–like glycogen that may damage affected tissues. The clinical manifestations of GSD IV are heterogeneous; one of which is the classic manifestation of progressive hepatic fibrosis. There is no specific treatment available for GSD IV. Currently, liver transplantation is an option. It is crucial to evaluate long–term outcomes of liver transplantation. We reviewed the published literature for GSD IV patients undergoing liver transplantation. To date, some successful liver transplantations have increased the quantity and quality of life in patients. Although the extrahepatic manifestations of GSD IV may still progress after transplantation, especially cardiomyopathy. Patients with cardiac involvement are candidates for cardiac transplantation. Liver transplantation remains the only effective therapeutic option for treatment of GSD IV. However, liver transplantation may not alter the extrahepatic progression of GSD IV. Patients should be carefully assessed before liver transplantation.